Occurrence of Aflatoxins in compound feeds and feed materials for dairy livestock in Central Greece - MANOURAS (Α. ΜΑΝΟΥΡΑΣ) A.; MALISSIOVA (Ε. ΜΑΛΙΣΣΙΟΒΑ) E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Aflatoxins (AFs) in feeds are considered as serious hazards for livestock health and additionally they pose a risk for consumers’ health, especially when contaminated milk is consumed. Since AFs toxicity and stability during feeds and food processing is well established, this study aimed to determine the level of AFs contamination in compound feeds, feed materials and silage, intended for feeding dairy livestock, in central Greece. Out of 274 feed samples analyzed with Enzyme Linked Immunosorbent Assay (ELISA), in 132 (48.17%) AFs were not detected, while 39 (14.23%) were found above the EU maximum tolerable limit of 10 μg kg-1. The levels of AFs contamination ranged from 0.6 to 45.2 μg kg-1. It was found more possible for corn to be contaminated (p-value<0.001). The relatively high incidence of AFs in feeds and especially in corn was verified in this study, something that is line with the view that Mediterranean countries are in high risk for AFs. As there are several factors affecting the level of AFs contamination, constant monitoring of AFs in feeds is required in order to prevent adverse effects on animals and additionally to act as a precaution measure for the occurrence of AFM1 in milk.